Measurement Levels of the Spatial Integration – Suggestions for a Central-European Factor Group - Andrea Uszkai (DETUROPE)
The objective of the study is to point out, what kind of measurement methodologies and factor groups are used to determinate the depth of the spatial integration in the national and international scientific literature. Integration means in this sense the interconnection of several (spatial) units (Kulcsár-Rostás, 1989; Kovács, 2001; Kiss, 2005). One of the most widely interpreted types of the integration is the economic integration, which can be applied to enterprises and spatial units as well. This study focuses on the last one and examines it at three territorial levels, distinguishing global, supranational (among national states) and subnational levels. The possible measurement methods are significantly determined by the spatial levels. The paper makes some suggestions for the possible measurement method in Cenrtral-European context.